⇒ To find f(4) it means that in the place of x in the function f plug in 4 and simplify to find f(4)
![f(4)=3(4)-4\\f(4)=12-4\\f(4)=8](https://img.qammunity.org/2023/formulas/mathematics/high-school/fjluebml7rus8tbrk548pcloz5grb9cjbo.png)
⇒Now let us find 2g(3),meaning in the place of x in the function g plug in 3 and simplify to find g(3) after that then multiply the results by 2 as indicated.
![g(3)=(3)-41\\g(3)=-38](https://img.qammunity.org/2023/formulas/mathematics/high-school/c1wop40rcqiinrqqk01oupm0wyixy3xn9m.png)
Meaning 2(g(3))= 2(-38)
⇒2(g(3))=-76
⇒N0ow let us find the value of f(4) - 2g(3)
⇒
![f(4) - 2g(3)=8-(-76)\\ f(4) - 2g(3)=8+76\\ f(4) - 2g(3)=84](https://img.qammunity.org/2023/formulas/mathematics/high-school/mexd3wb9fl5nn6feiw41jwz4eud31mwgco.png)
⇒The answer is 84